A scoping review of Aboriginal and Torres Strait Islander health promotion programs focused on modifying chronic disease risk factors. (9th December 2019) - Canuto, Karla J.; Aromataris, Edoardo; Burgess, Teresa; Davy, Carol; McKivett, Andrea; Schwartzkopff, Kate; Canuto, Kootsy; Tufanaru, Catalin; Lockwood, Craig; Brown, Alex
Abstract: Issue addressed: Noncommunicable chronic disease underlies much of the life expectancy gap experienced by Aboriginal and Torres Strait Islander people. Modifying contributing risk factors; tobacco smoking, nutrition, alcohol consumption, physical activity, social and emotional wellbeing (SNAPS) could help close this disease gap. This scoping review identified and describes SNAPS health promotion programs implemented for Aboriginal and Torres Strait Islander people in Australia. Methods: Databases PubMed, CINAHL, Informit (Health Collection and Indigenous Peoples Collection), Scopus, Trove and relevant websites and clearing houses were searched for eligible studies until June 2015. To meet the inclusion criteria the program had to focus on modifying one of the SNAPS risk factors and the majority of participants had to identify as being of Aboriginal and/or Torres Strait Islander heritage. Results: The review identified 71 health promotion programs, described in 83 publications. Programs were implemented across a range of health and community settings and included all Australian states and territories, from major cities to remote communities. The SNAPS factor addressed most commonly was nutrition. Some programs included the whole community, or had multiple key audiences, whilst others focused solely on one subgroup of the population such as chronic disease patients, pregnant women or youth. Fourteen of the programs reported no outcome assessments. Conclusions: Health promotion programs for Aboriginal and Torres Strait Islander people have not been adequately evaluated. The majority of programs focused on the development of individual skills and changing personal behaviours without addressing the other health promotion action areas, such as creating supportive environments or reorienting health care services. So What?: This scoping review provides a summary of the health promotion programs that have been delivered in Australia for Aboriginal and Torres Strait Islander people to prevent or manage chronic disease. These programs, although many are limited in quality, should be used to inform future programs. To improve evidence‐based health promotion practice, health promotion initiatives need to be evaluated and the findings published publicly.